A cobertura natural, o potencial paisagístico e turismo no Parque Nacional do Caparaó (ES-MG) segundo a hierarquia de paisagens de Georges Bertrand (1972) - Massini, Victor Silveira (2017)
This research intends to study the Conservation Unit (UC) named Parque Nacional do Caparaó (PNC), located in an area that covers both the states of Espírito Santo and Minas Gerais (Brazil), inspired by the General Systems Theory for Geographic Science. It´s attempted to conform the studied area as a Natural Region on the Hierarchization of Landscape Scale, according to the theoretical proposal by Georges Bertrand (1972; 2004), and comprehend the relation between the ecological potential, the biological exploration and the anthropic action that occur in the UC. For the understanding of the area the research proposed the identification, the classification and the mapping of the natural coverage and other uses on PNC, based on fitofisionomic systems developed by Carlos Rizzini (1979) and Afrânio Fernandes (2007; 2006). In this manner, getting to know the real distribution and composition of the vegetative mosaic in the park, it was attempted to integrate such information with the pre-structured interviews carried out with the representative of its managing body, as well as with entrepreneurs in the tourism sector on the region of Caparaó capixaba